2023
DOI: 10.3926/jotse.1806
|View full text |Cite
|
Sign up to set email alerts
|

Application of the flipped classroom model to stimulate university students’ learning with online education

Abstract: This work sets out the results of a teaching innovation project applying the flipped classroom model in the Knowledge of Mathematics module on a bachelor’s degree in primary education over two consecutive years at a university that exclusively uses online teaching. This model is used with the aim of stimulating the students’ working methods and improve their intrinsic motivation. The research evaluates the impact of the flipped classroom on academic performance in the subject and collects information on studen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…We will also run a series of activity based workshops using a flipped classroom model where students will work through material from the OER before attending (Reidsema, Hadgraft, & Kavanagh, 2017). It is hoped this will better prepare students for the workshops, increase engagement and enable them to clarify any issues to reinforce their learning (Cuetos, 2023). Finally, given our students are spread across the state studying on campus or online, we believe the flipped classroom model will be a more equitable learning experience (Willis, 2017).…”
Section: Future Plansmentioning
confidence: 99%
“…We will also run a series of activity based workshops using a flipped classroom model where students will work through material from the OER before attending (Reidsema, Hadgraft, & Kavanagh, 2017). It is hoped this will better prepare students for the workshops, increase engagement and enable them to clarify any issues to reinforce their learning (Cuetos, 2023). Finally, given our students are spread across the state studying on campus or online, we believe the flipped classroom model will be a more equitable learning experience (Willis, 2017).…”
Section: Future Plansmentioning
confidence: 99%
“…In biology instruction, Flores-González and Flores-González 2 found that the flipped classroom fosters self-regulated learning and active engagement among students. Within an online educational environment, Cuetos 3 research indicates that the flipped classroom model elevates university students’ learning motivation and academic achievement. In the field of English teaching, Dewi et al 4 study also revealed that students hold a positive attitude towards the new teaching mode of the flipped classroom.…”
Section: Introductionmentioning
confidence: 99%